Transfixed in Lesbian Paradise - Salah, Trish (Atlantis)

(untitled) (Mount Saint Vincent University, 2007)
This narrative essay reflects upon experiences at the Toronto Women's Bathhouse to think about asymmetrical conditions of trans inclusion in lesbian erotic and cultural spaces. It queries the affective disjunctures between formal policies of trans-inclusion in women's spaces and "on the ground" interpersonal recognition of trans women as women and of trans men as men.